Digitalisasi Perhitungan Harga Pokok Produksi Minyak Senggugu Menggunakan Metode Full Costing Pada CV Tujuh Putik - syarif, muhamad; Risdiansyah, Deni (Jurnal Sistem Informasi Akuntansi, 2023)
Senggugu oil production by CV Tujuh Putik requires increased efficiency in managing the calculation of the cost of production. Manuality in the cost calculation process hinders the potential for increasing profits. Therefore, digitalization is considered as a solution to increase the accuracy, speed and affordability of information related to HPP. The background to the need for digitalization is the problems that occur, namely delays, calculation errors and inaccurate cost information. A new approach is needed that integrates digital technology to update the calculation system to be more efficient and responsive to business needs, increase the accuracy of production cost calculations, speed up the decision-making process, and provide a stronger information foundation for the company's business strategy. This research aims to implement digitalization in the calculation of Senggugu oil HPP at CV Tujuh Putik using the Full Costing method. By implementing digital technology, it is hoped that it can open up new efficiency opportunities and strengthen the company's competitiveness in a dynamic market.